Enhancing linkages : a new vision for trade (2013)
Examines the notion of structured trade, that is, trade organised between different interdependent stakeholders within a sector - farmers, transporters, traders, warehouse managers, bankers, processors, agribusiness agents and community exchange operators - and its benefits to these stakeholders.
Keywords: AGRICULTURAL TRADE